2009
DOI: 10.2217/fmb.09.107
|View full text |Cite
|
Sign up to set email alerts
|

Defensins Attenuate Cytokine Responses Yet Enhance Antibody Responses to Porphyromonas Gingivalis Adhesins in Mice

Abstract: Aim-Our aim is to assess the ability of human neutrophil peptide α-defensins (HNPs) and human β-defensins (HBDs) to attenuate proinflammatory cytokine responses and enhance antibody responses to recombinant hemagglutinin B (rHagB) or recombinant fimbrillin A (rFimA) from Porphyromonas gingivalis 381 in mice.Materials & methods-In the first study, C57BL/6 mice were given 10 μg rHagB or rFimA without and with 1 μg HNP1, HNP2, HBD1, HBD2 or HBD3. At 24 h, mice were euthanized and cytokine concentrations were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
1
21
0
1
Order By: Relevance
“…HNP-1 has been shown to block the ATP-induced IL-1β release from lipopolysaccharide (LPS)-activated human monocytes (31). In another study, HNP-1 and HNP-2 attenuated IL-6 and keratinocyte-derived chemokine responses to recombinant hemagglutinin B from Porphyromonas gingivalis (rHagB) (32). HNP-1-3 reduced the production of several pro-inflammatory cytokines, including TNF-α, from LPS- or CD40L/interferon-γ-stimulated human monocyte-derived macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…HNP-1 has been shown to block the ATP-induced IL-1β release from lipopolysaccharide (LPS)-activated human monocytes (31). In another study, HNP-1 and HNP-2 attenuated IL-6 and keratinocyte-derived chemokine responses to recombinant hemagglutinin B from Porphyromonas gingivalis (rHagB) (32). HNP-1-3 reduced the production of several pro-inflammatory cytokines, including TNF-α, from LPS- or CD40L/interferon-γ-stimulated human monocyte-derived macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, several recent reports have shown that low levels of HNP 1 could suppress the release of pro-inflammatory cytokines such as IL-1β, IL-6, and TNF-α [21][22][23] and increase IL-10 mRNA expression in the intestinal tissue [18] . These results demonstrate that HNPs have immunomodulatory effects that are concentration dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that further prophylactic and therapeutic approaches against periodontal diseases associated with P. gingivalis could be developed based on hemagglutinins. For example, human alpha- and beta- defensins were shown to bind P. gingivalis rHagB and enhance the IgG response in mice which could potentially lead to P. gingivalis clearance from the host [5859]. HagA has been recognized by serum from a periodontal patient while we have previously reported that HagA expression in a S. enterica serovar Enterica vaccine strain was able to induce a humoral immune response against this hemagglutinin [40].…”
Section: Discussionmentioning
confidence: 99%